تصميم بيئة تعلم إلكتروني تكيفية وفقا لأساليب التعلم المفضلة باستخدام النظرية التواصلية لتنمية التحصيل المعرفي في العلوم ومفهوم الذات لدى الطلاب بطيئي التعلم - سلامة، حسن علي حسن Salamah, Hasan Ali Hasan; عطية، يسري مصطفى السيد; عبدالغني، محمود جابر محمود (جامعة سوهاج - كلية التربية, 2023)
استهدف البحث تصميم بيئة تعلم إلكتروني تكيفية وفقاً لأساليب التعلم المفضلة في ضوء النظرية التواصلية وقياس أثرها في تنمية التحصيل المعرفي في العلوم ومفهوم الذات لدى الطلاب بطيئي التعلم بالصف الأول الإعدادي؛ ولتحقيق أهداف البحث استخدم منهج البحث التطويري، وذلك بتطبيق نموذج محمد إبراهيم الدسوقي (۲۰۱٤) لتصميم وإنتاج بيئات التعليم والتعلم الإلكتروني، وتم بإعداد مواد البحث تمثلت في بيئة التعلم الإلكتروني التكيفية وفقاً لأساليب التعلم المفضلة باستخدام النظرية التواصلية، وقائمة معايير تصميم بيئة التعلم الإلكتروني التكيفية وفقاً لأساليب التعلم المفضلة باستخدام النظرية التواصلية، واختبار التحصيل المعرفي، لقياس الجانب المعرفي في مقرر العلوم، وتكونت عينة البحث من ( ۲۲ ) طالب من بطيئي التعلم، وتوصلت نتائج البحث إلى وجود فرق ذو دلالة إحصائية بين متوسطي درجات الطلاب عينة البحث في التطبيقين القبلي والبعدي لاختبار التحصيل المعرفي في العلوم لصالح التطبيق البعدي، ووجود فرق ذو دلالة إحصائية بين متوسطي درجات الطلاب عينة البحث في التطبيقين القبلي والبعدي لمقياس مفهوم الذات، لصالح التطبيق البعدي. The research aimed to design an adaptive e-learning environment according to the preferred learning methods in the light of Connectivism Theory and measure its impact on the development of cognitive achievement in science and self-concept among slow learners in the first grade of preparatory school. To achieve the objectives of the research, the researcher used the developmental research approach, by applying the model of Muhammad Ibrahim Al-Dasouki (2014) to design and produce educational and e-learning environments. adaptive according to the preferred learning methods using Connectivism Theory, and cognitive achievement test, to measure the cognitive aspect in the science course, and the research sample consisted of (22) students who are slow learners, and the results of the research concluded that there is a statistically significant difference between the mean scores of the students of the research sample in the two pre-applications and post-test of cognitive achievement in science, and the difference was in favor of the post-application, and the results confirmed the existence of a statistically significant difference between the mean scores of the students of the research sample in the pre and post applications of the self-concept scale, and the difference was in favor of the post-application.
Keywords: التعليم الإلكتروني -- بطء التعلم -- مادة العلوم -- التحصيل الدراسي -- التعليم الإعدادي